Recreational forest: design with nature: designing recreational areas at natural rainforest in Panti Recreational Forest, Kota Tinggi, Johor/ Mohamad Nazarudin Jumaat - Jumaat, Mohamad Nazarudin (2019)
The natural tropical rainforest providing diverse and educational environment which growth the social integration to sustain the ecosystem and living thing. To increase the sense of belonging and improve the awareness from community, research and educational purpose to encourage user appreciate natural environment. Forest protection are one of important role to reconnect the nature with user. To generate the conservation and preservation strategies, "Ian McHarg's Ecological Inventory Method" have been used for proposed strategies. From this study, to emphasis this forest as one attraction for urban escape is generate the sustainable protection for flora and fauna. On that, this forest implement the water filter with natural approach to increase natural habitat, generate natural activities with design based on nature and forest functional as natural tourism spot for community and tourist. In that fact, the nature also giving the positive implications toward surrounding, fair as educational and research center for nature lovers, promoting the sustainable activities, and accessible for encourage the flora and fauna growth. Thus, the strong natural treasure identity and genius loci can be implement to increase nature value. Therefore, to having the benefit of forest landscape show the present natural element can generate the ideas to produce the magnificent natural rainforest environment in Panti Recreational Forest.